Did the celtic tiger decrease socio-economic differentials in perinatal mortality in Ireland? - Richard Layte; Barbara Clyne (The Economic and Social Research Institute (ESRI), 2009)
Irish perinatal mortality rates have been falling steadily for a number of decades but evidence from the 1980s showed pronounced differentials in mortality rates across socio-economic groups. Between 1995 and 2007 Irish gross national product increased from 60 per cent of the EU average to 110 per cent. Real incomes increased across the income distribution during this period but income inequality between the top and bottom income deciles increased. This paper examines whether this increase in affluence led to an overall improvement in Irish perinatal mortality rates and the extent to which any improvement was shared across socio-economic groups. This task is complicated by demographic change in Ireland since the 1980s and its interaction with the birth registration process. Overall perinatal mortality rates have fallen from 14 per 1,000 in 1984 to 7 per 1,000 in 2006. Without adjusting for demographic change differentials between professional and unskilled/unemployed groups have decreased from 1.99 to 1.79. Adjusted estimates suggest the real differential has decreased to 1.88.
Keywords: 330; Wirtschaftswachstum; Sozialprodukt; Einkommensverteilung; Schwangerschaft; Kindersterblichkeit; Irland